Nucleotide Excision Repair, Mismatch Repair, and R-Loops Modulate Convergent Transcription-Induced Cell Death and Repeat Instability - Lin, Yunfu; Wilson, John H. (PLOS ONE, 2012)
Expansion of CAG•CTG tracts located in specific genes is responsible for 13 human neurodegenerative disorders, the pathogenic mechanisms of which are not yet well defined. These disease genes are ubiquitously expressed in human tissues, and transcription has been identified as one of the major pathways destabilizing the repeats. Transcription-induced repeat instability depends on transcription-coupled nucleotide excision repair (TC-NER), the mismatch repair (MMR) recognition component MSH2/MSH3, and RNA/DNA hybrids (R-loops). Recently, we reported that simultaneous sense and antisense transcription–convergent transcription–through a CAG repeat not only promotes repeat instability, but also induces a cell stress response, which arrests the cell cycle and eventually leads to massive cell death via apoptosis. Here, we use siRNA knockdowns to investigate whether NER, MMR, and R-loops also modulate convergent-transcription-induced cell death and repeat instability. We find that siRNA-mediated depletion of TC-NER components increases convergent transcription-induced cell death, as does the simultaneous depletion of RNase H1 and RNase H2A. In contrast, depletion of MSH2 decreases cell death. These results identify TC-NER, MMR recognition, and R-loops as modulators of convergent transcription-induced cell death and shed light on the molecular mechanism involved. We also find that the TC-NER pathway, MSH2, and R-loops modulate convergent transcription-induced repeat instability. These observations link the mechanisms of convergent transcription-induced repeat instability and convergent transcription-induced cell death, suggesting that a common structure may trigger both outcomes.